A Zn(II) luminescent polymer as a multifunctional sensor to nitrobenzene, Fe3+ and CrO42− ions. Issue 19 (1st October 2016) - Wang, Jun; Lu, Lu; Wu, Wei-Ping; Hu, Huai-Ming; Xie, Bin
Abstract: A metal-organic framework of {[Zn(tib)2 ]·2NO3 } (tib = 135-tris(1-imidazolyl)benzene) (1 ) has been synthesized and characterized. The structure determination reveals that1 is a 2-D layer network and exhibits a classicalhxl topology.1 shows selective properties in the detection of nitrobenzene and Fe 3+ . Furthermore, 1 also exhibits an excellent capability to detect CrO4 2− . The present work indicates that1 could be taken as a potential candidate for developing multifunctional luminescence sensors. Abstract :